Long-Term Visual Quality and Pupil Changes after Small-Incision Lenticule Extraction for Eyes without Preoperative Cylinder Refraction - Xiaonan Yang; Qiting Feng; Quan Liu; Jianhui Chen; Pengxia Wan (Journal of Ophthalmology)
Purpose. To investigate the long-term changes in visual quality and pupil size after small incision lenticule extraction (SMILE) for eyes without preoperative cylinder refraction. Methods. Thirty-three myopic eyes (33 patients) without preoperative cylinder refraction were corrected using SMILE. Refractive outcomes, corneal curvature, aberrations, contrast sensitivity (CS), and pupil diameter were evaluated preoperatively, and 30 months postoperatively. Results. The 30-month postoperative uncorrected and corrected distance visual acuity (UDVA and CDVA, LogMAR) were −0.10 ± 0.09 and −0.14 ± 0.06, respectively, whereas the preoperative CDVA (LogMAR) was −0.07 ± 0.05. Cylinder refraction of −0.11 ± 0.21 D (ranging from −0.50 to 0.00) was observed at 30 months postoperatively, increasing from the preoperative cylinder refraction of 0.00 ± 0.00 D (P=0.004). Moreover, the centroid coordinates x, y of corneal anterior astigmatic vectors were −0.19 ± 0.22, 0.81 ± 0.33 at 30 months postoperatively, and 0.02 ± 0.28, 0.76 ± 0.51 preoperatively (Px<0.001 and Py=0.810, respectively). Furthermore, a 15° axis change in the mean anterior corneal astigmatic vector was observed at 30 months postoperatively from the preoperative state, as measured by Pentacam. At 30 months postoperatively, the photopic Log CS reduced significantly with glare at three and six cycles/degrees (P<0.001 and P=0.015, respectively), a decreased photopic pupil diameter (3.27 ± 0.55 mm vs. 3.10 ± 0.66 mm, P=0.030), and an increased Coma (Z31) and Trefoil (Z3−3) at 4 mm diameter area analysis. However, a significant linear regression relationship was only observed between changes in photopic pupil diameter and changes in photopic Log CS with glare at 12 cycles/degree (P=0.038 and β = 0.282). Conclusion. Slight cylinder regression was observed with thicker corneal lenticular extraction after SMILE correction of nonastigmatic eyes 30 months postoperatively. This regression was mainly because of the axis changes in anterior corneal astigmatism power. Therefore, a cylinder nomogram modification of 0.25 to 0.50 D is considerable for correcting nonastigmatic myopic eyes with a predicted spherical lenticular thickness over 100 µm.